Seasonal Variations of the Gravity Wave Momentum Flux in the Antarctic Mesosphere and Lower Thermosphere - Espy, P. J.; Jones, G. O.L.; Swenson, G. R.; Tang, J.; Taylor, Michael J. (Journal of Geophysical Research: Atmospheres, 2004)
Airglow imager and dynasonde/imaging Doppler interferometer (IDI) radar wind measurements at Halley Station, Antarctica (75.6S, 26.6W) have been used to estimate the seasonal variation of the vertical fluxes of horizontal momentum carried by highfrequency atmospheric gravity waves. The cross-correlation coefficients between the vertical and horizontal wind perturbations were calculated from sodium (Na) airglow imager data collected during the austral winter seasons of 2000 and 2001. These were combined with wind velocity variances from coincident radar measurements to estimate the daily averaged upper limit of the vertical flux of horizontal momentum due to gravity waves. The resulting momentum flux at the Na airglow altitudes, while displaying a large day-to-day variability, showed a marked rotation from the northwest to the southeast throughout the winter season. Calculations show that this rotation is consistent with seasonal changes in the wind field filtering of gravity waves below the Na airglow region. The calculations also indicate that while the magnitude of the meridional wind is small, this filtering leads to the observed seasonal changes in the meridional momentum flux.